Historical volatile organic compounds emission performance and reduction potentials in China's petroleum refining industry. (10th April 2021) - Simayi, Maimaiti; Hao, Yufang; Li, Jing; Shi, Yuqi; Ren, Jie; Xi, Ziyan; Xie, Shaodong
Abstract: The petroleum refining industry in China is a major contributor to the national economy and a significant source of ambient volatile organic compounds (VOCs). The development history of China's refineries was investigated for the period 1949–2018, and future development trends were predicted until 2030. The historical VOC emissions from 1949 to 2018 were estimated based on source-specific emission factors, and the emissions in 2025 and 2030 were predicted under the business-as-usual (BAU), alternative control (AC), and accelerated control (ACC) scenarios. Each scenario consisted of a policy and a technical scenario. VOC emissions from refineries increased from 0.53 Gg in 1949 to 1.12 Tg in 2018; fugitive emissions were always the most significant sources of VOCs (40.0–43.9%), followed by end-of-pipe (28.4–31.3%), tank storage (18.3–25.3%), and wastewater treatment (5.8–6.6%) emissions. Provinces in the coastal area have experienced more VOC emissions than inland areas, and Eastern China currently has the highest VOC emissions from refineries. By 2030, China could reduce its current VOC emissions by 5.4%, 35.7%, and 62.5% under the BAU, AC, and ACC scenarios, respectively. The main pressure for reducing VOC emission from China's refineries will come predominantly from Northeastern China, followed by Eastern and Northern China. The improvement of the production processes, enhancing the airtightness of equipment and containers, and implementation of improved leak detection and repair system are the more effective measures in reducing VOC emissions, accounting for more than 40% of the total reduction. In addition, the penetration and removal rate of control measures for end-of-pipe sources should be further strengthened.